Multi-stage thermal modelling of extrusion-based polymer additive manufacturing - Yang, Jiong (2023)
Additive manufacturing is one the most promising fabrication strategies for the fabrication of bone tissue scaffolds using biodegradable semi-crystalline polymers. During the fabrication process, polymeric material in a molten state is deposited in a platform and starts to solidify while cooling down. The build-up of consecutive layers reheats the previously deposited material, introducing a complex thermal cycle with impacts on the overall properties of printed scaffolds. Therefore, the accurate prediction of these thermal cycles is significantly important to properly design the additively manufactured polymer scaffolds and the bonding between the layers. This paper presents a novel multi-stage numerical model, integrating a 2D representation of the dynamic deposition process and a 3D thermal evolution model to simulate the fabrication process. Numerical simulations show how the deposition velocity controls the spatial dimensions of the individual deposition layers and the cooling process when consecutive layers are deposited during polymer printing. Moreover, numerical results show a good agreement with experimental results.